2016
DOI: 10.1037/neu0000242
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness in frontoparietal and cingulo-opercular networks predicts executive function performance in older adults.

Abstract: This study examined the relationship between cortical thickness in executive control networks and neuropsychological measures of executive function. Method: Forty-one community-dwelling older adults completed an MRI scan and a neuropsychological battery including 5 measures of executive function. Results: Factor analysis of executive function measures revealed 2 distinct factors: (a) Complex Attention Control (CAC), comprised of tasks that required immediate response to stimuli and involved subtle performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 62 publications
7
33
1
4
Order By: Relevance
“…The executive network is involved in error detection, resolving conflict and other aspects of performance [5**, 6, 7]. The executive network is present in infancy, with the areas activated by perceived error similar in adults and infants, including the anterior cingulate cortex (ACC) [8].…”
Section: Development Of Attentional Networkmentioning
confidence: 99%
“…The executive network is involved in error detection, resolving conflict and other aspects of performance [5**, 6, 7]. The executive network is present in infancy, with the areas activated by perceived error similar in adults and infants, including the anterior cingulate cortex (ACC) [8].…”
Section: Development Of Attentional Networkmentioning
confidence: 99%
“…Blood-oxygen-level-dependent (BOLD) signal from the cerebral white matter and ventricles was removed prior to seed-based connectivity analysis using principal component analysis of the multivariate BOLD signal within each these masks obtained from the segmented T1weighted MPRAGE scans (Fallon et al, 2016;Woodward, Rogers, & Heckers, 2011). These networks were chosen as they have been intimately associated with aspects of cognitive functioning disrupted in NDfE (Aikia et al, 1995(Aikia et al, , 2001Ichesco et al, 2012;Kalviainen et al, 1992;Markett et al, 2014;Menon, 2015;Prevey et al, 1998;Pulliainen et al, 2000;Schmidt et al, 2016;Taylor et al, 2010) and/or have been demonstrated to be significantly altered in refractory epilepsy (de Campos et al, 2016;Kay et al, 2013;Wei et al, 2015). We generated seed-to-voxel connectivity maps for each individual for the following reproducibly demonstrated functional networks: the default mode, salience, fronto-parietal attention, language, and sensorimotor networks.…”
Section: Resting-state Functional Analysismentioning
confidence: 99%
“…We generated seed-to-voxel connectivity maps for each individual for the following reproducibly demonstrated functional networks: the default mode, salience, fronto-parietal attention, language, and sensorimotor networks. These networks were chosen as they have been intimately associated with aspects of cognitive functioning disrupted in NDfE (Aikia et al, 1995(Aikia et al, , 2001Ichesco et al, 2012;Kalviainen et al, 1992;Markett et al, 2014;Menon, 2015;Prevey et al, 1998;Pulliainen et al, 2000;Schmidt et al, 2016;Taylor et al, 2010) and/or have been demonstrated to be significantly altered in refractory epilepsy (de Campos et al, 2016;Kay et al, 2013;Wei et al, 2015). Seeds were 10-mm-diameter spheres; the spatial coordinates and anatomical location of network seeds are provided in Table 2 and illustrated in Figure 1.…”
Section: Resting-state Functional Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(Milner, 1982;Donders & Kirsch, 1991;Ardila et al, 2000;Friedman et al, 2006;Arffa, 2007;O'Reilly, 2010;Verdejo-García & Bechara, 2010;Stuss, 2011;Flores Lázaro, Tinajero Carrasco, & Castro Ruiz, 2011;Schmidt, Burge, Visscher, & Ross, 2016).…”
Section: Introductionunclassified